Legal Foundation of the Principle of the Responsibility to Protect - Zangeneh, Basharat Reda (Journal of Legal and Political Studies, 2015)
After accreditation the charter of the United Nations and determining the legal principles and developing the concept of intervention in order to containing several cases, like intervene to confine Genocide and atrocities and intervene to accessing humanitarian aids, along with the efforts to respecting human rights and disposal the breaches. but the intervention problem, either in peaceful way or militaries way or by authorizing or without authority, consider as an legal paradigm which overwhelmingly contrast with the principle of national sovereignty and the principle of Non-intervention. in addition of the practical problems of intervention which have inverse effects on human rights and doubling the tragedies some times.So these problems attached with the principle of Responsibility to Protection (R2P), which aims to stopping and extreme atrocities and human rights violence which commit until nowadays. therefore the United Nations declarated formally in 2005 summit, an aiming idea to protect the civilians which means that the sovereignty does not means only a right, but also it contains the concept of responsibility which necessitate the duty of protecting the citizens, and this duty will focus on prohibiting and confine the crimes of: Genocide, War crimes, crimes against Humanity and Ethnic cleansing, under the name Principle of Responsibility to Protection. so the importance of this study increasing along with the international community attitude to offering human security and civilian protection after the touched developments concerning the national sovereignty of states, which doesn't remain no longer as a paravent that the governances hidden behind it and commit atrocities and breaches against citizens' rights.
Keywords: United Nations; humanitarian aids; Nonintervention; human rights